2015
DOI: 10.7314/apjcp.2015.16.15.6627
|View full text |Cite
|
Sign up to set email alerts
|

Decitabine in the Treatment of Acute Myeloid Leukemia and Myelodysplastic Syndromes, Which Combined with Complex Karyotype Respectively

Abstract: Background:We conducted a study exploring the clinical safety and efficacy of decitabine in patients with acute myeloid leukemia (AML) and myelodysplastic syndromes (MDS), combined with a complex karyotype. Materials and Methods: From April 2009 to September 2013, a total of 35 patients with AML/MDS combined with a complex karyotype diagnosed in the First Affiliated Hospital of Soochow University were included for retrospective analysis. All patients were treated with decitabine alone (20mg/m 2 daily for 5 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In our study, TP53 mutations were associated with increases in CRs to DAC therapy, particularly in individuals with TP53 mutations and complex karyotypes (involving abnormalities on chromosomes 5 and/or 7 or containing monosomies) (Table S3). Other studies (Gao et al, 2015;Lubbert et al, 2016) have reported higher levels of responsiveness toward DAC among MDS patients with poor karyotypes (complex karyotypes, chromosome 7 abnormalities, or monosomies). Because TP53 mutations frequently coincide with complex karyotypes, it is understandable that MDS patients with TP53 mutations are especially sensitive to DAC therapy.…”
Section: Discussionmentioning
confidence: 92%
“…In our study, TP53 mutations were associated with increases in CRs to DAC therapy, particularly in individuals with TP53 mutations and complex karyotypes (involving abnormalities on chromosomes 5 and/or 7 or containing monosomies) (Table S3). Other studies (Gao et al, 2015;Lubbert et al, 2016) have reported higher levels of responsiveness toward DAC among MDS patients with poor karyotypes (complex karyotypes, chromosome 7 abnormalities, or monosomies). Because TP53 mutations frequently coincide with complex karyotypes, it is understandable that MDS patients with TP53 mutations are especially sensitive to DAC therapy.…”
Section: Discussionmentioning
confidence: 92%
“…Myelodysplasia is a heterogeneous disease with an increased risk of leukemic transformation, overall 40% of patients will transform to AML during the disease course (Chevassut et al, 2011;Gao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested that decitabine monotherapy is a better choice for MDS patients with poor karyotypes (Li et al 2013; Lubbert et al 2001; Wu et al 2016). Several studies showed that decitabine in combination with CAG could achieve 50–70% CR in AML and MDS patients with complex karyotypes (Gao et al 2015; Li et al 2015). Gao et al also noted an association of treatment response with the number of courses in AML and MDS patients with complex karyotypes (Gao et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that decitabine in combination with CAG could achieve 50–70% CR in AML and MDS patients with complex karyotypes (Gao et al 2015; Li et al 2015). Gao et al also noted an association of treatment response with the number of courses in AML and MDS patients with complex karyotypes (Gao et al 2015). Patients with poor karyotypes who received decitabine in combination with CAG tended to have a longer OS (Li et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation